Computer Implementation of the New Diabetes Classification Scheme - Wiener, F.; Kanter, Y.; Kol, S.; Barzilai, D. (Methods of Information in Medicine, 1982)
The classification of diabetes and other categories of glucose intolerance developed by the international workgroup sponsored by the National Diabetes Data Group of the NIH has been implemented on the computer, using a system for the simulation of medical reasoning. The system allows the physician to formulate his medical knowledge as a series of logical inferences and to specify those combinations of clinical findings which confirm or reject each inference. Alphabetical lists of the texts of medical statements appearing in the knowledge base are used to specify patient data. A patient status report is produced by comparing the patient data with the medical logic. The report lists patient data, the inferences confirmed and, if necessary, requests additional data to complete the classification. The system has enabled us to computerize the new classification scheme in a relatively short time and with a minimum of effort. The system has correctly classified nearly 100 patients on our ward and in the endocrinology clinics using data routinely recorded. The computer evaluation is now an integral part of the patient record. It assures that the new classification scheme is applied to all patients in an unbiased and consistent manner.
Keywords: Diabetes Classification; Computer Simulation of Medical Reasoning; Medical Logic Modules; Diagnosis by Logical Inference; Symptom Combinations